2007
DOI: 10.1016/j.jaci.2006.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Allergen-dependent solubilization of IL-13 receptor α2 reveals a novel mechanism to regulate allergy

Abstract: Background-Allergic sensitization affects half of western populations and often precedes the development of allergic disorders including asthma. Despite the critical role of allergens in the pathogenesis of these disorders, little is known about how allergens modulate the immune response. IL-13 receptor α2 (IL-13Rα2) is a decoy receptor for IL-13. Objective: Although the existence of soluble IL-13Rα2 has been documented, the mechanisms underlying its generation are unknown. Many allergens possess protease acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Human IL-13Rα2 was detected by ELISA, as previously described (31), modified only by the use of polyclonal goat anti-human IL-13Rα2 (1 μg/ml; R&D Systems, Minneapolis, MN) for the capture Ab. The standard curve was linear from 100–8000 pg/ml.…”
Section: Methodsmentioning
confidence: 99%
“…Human IL-13Rα2 was detected by ELISA, as previously described (31), modified only by the use of polyclonal goat anti-human IL-13Rα2 (1 μg/ml; R&D Systems, Minneapolis, MN) for the capture Ab. The standard curve was linear from 100–8000 pg/ml.…”
Section: Methodsmentioning
confidence: 99%
“…Our results are consistent with those reported by Munitz et al [27] who demonstrated that mucus gene upregulation in a mouse model of allergic lung inflammation is dependent on IL-13Rα1. Further studies to investigate the role of IL-13Rα2 in allergic lung inflammation models driven by house dust mite, an aeroallergen shown to cleave IL-13Rα2 from the cell surface [28], and that stimulates robust fibrosis, angiogenesis and airways hyperreactivity in mice [29], are planned.…”
Section: Discussionmentioning
confidence: 99%
“…Matsumura et al [20] reported that endogenous MMP(s) [matrix metalloproteinase(s)] solubilize IL-13Rα2 in airway epithelial cells, whereas Chen et al [21] demonstrated that soluble IL-13Rα2 can be produced by means of direct cleavage by MMP-8 and that MMP-8 contributes to the solubilization of IL-13Rα2 in BALF (bronchoalveolar lavage fluid) in house dust mite-treated mice. Furthermore, this group showed that exposure to mould or house dust mite allergens resulted in degradation of surface IL-13Rα2 [22]. This reduction in receptor levels may contribute to the pathogenesis of allergic disorders in individuals with allergy because of the loss of IL-13Rα2 inhibition of IL-13 responses.…”
Section: Il-13rα2mentioning
confidence: 96%